The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1111/j.1365-2303.2012.01000.x
|View full text |Cite
|
Sign up to set email alerts
|

The positive impact of cytological specimens for EGFR mutation testing in non‐small cell lung cancer: a single South East Asian laboratory’s analysis of 670 cases

Abstract: Utilizing cytology samples for EGFR testing avoids unnecessary patient re-biopsing and yields a clinically superior satisfactory rate to the overall satisfactory rate of tissue biopsies of NSCLC. The quality rather than quantity of DNA extracted may be a more important determinant of a satisfactory result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
68
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 21 publications
7
68
0
1
Order By: Relevance
“…Although, we did not compare pyrosequencing with other methods, pyrosequencing method is sensitive in detecting both EGFR and KRAS mutations. Similar to previous reports, EGFR mutations were prevalent in nonsmokers (65.43%, P < 0.001), whereas KRAS mutations were common in smokers (67.85%, P < 0.001), and the two mutations are mutually exclusive in our study (6)(7)(8)25,29).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although, we did not compare pyrosequencing with other methods, pyrosequencing method is sensitive in detecting both EGFR and KRAS mutations. Similar to previous reports, EGFR mutations were prevalent in nonsmokers (65.43%, P < 0.001), whereas KRAS mutations were common in smokers (67.85%, P < 0.001), and the two mutations are mutually exclusive in our study (6)(7)(8)25,29).…”
Section: Discussionsupporting
confidence: 91%
“…The utility of cytology samples in detecting mutations in lung cancer have recently been increased and relatively widely investigated (8,(30)(31)(32). Cytology samples are especially useful in The present study showed that cytology specimens are comparable, or even better than non-cytology specimens, in detecting both EGFR and KRAS mutations.…”
Section: Discussionsupporting
confidence: 50%
“…The sensitivity of molecular application on cytological material may vary depending on the methodology used, which raises the need to properly validate the molecular procedure in every laboratory [33,34]. Fine-needle aspiration biopsy sampling represents an effective alternative with high DNA and RNA quality even in the close future with the perspective of obtaining neoplastic cells for genome sequencing using next-generation sequencing and outstanding results in the lung cancer field, too [35].…”
Section: Discussionmentioning
confidence: 99%
“…First, the nature of retrospective study will induce the collection bias. Second, the cytological samples varies, thus the tumor cell numbers, tumor percentages or DNA concentrations differs, which might affect the sensitivity of EGFR mutation detection (Pang et al, 2012;Khode et al, 2013;Jing et al, 2013). Third, not all of paired samples were collected simultaneously at a same location, the phenomenon of heterogeneity could has an impact on the detection result of EGFR mutation.…”
Section: Concordance Rate Of Egfr Mutations Between 101 Lbc Samples Amentioning
confidence: 99%